Systematic review of melasma treatments: advantages and disadvantages - Suryantari, Sang Ayu Arta; Sweta, Ni Putu Tamara Bidari; Veronica, Elvina; Hartawan, I Gusti Ngurah Bagus Rai Mulya; Karna, Ni Luh Putu Ratih Vibriyanti (DiscoverSys Inc, 2020)
Background: Melasma is an acquired chronic hyperpigmentation mostly affecting women. The pathogenesis of melasma is uncertain but it predominant related to ultraviolet (UV) exposure. Due to chronic and relapsing nature, melasma is challenging to treat. The current available treatment often has undesirable side effects and suboptimal results. The principal of treatment includes protect from UV radiation, inhibit melanin synthesize and increase pathway to remove melanin. Objectives: To define available treatments for melasma and determine advantages and disadvantages including topical, oral and procedural. Method: Medline, Cochrane library and PubMed database were searched for articles from January 2011 to June 2020. Only RCTs, comparative, prospective, retrospective and systematic reviews focusing on melasma treatments were extracted, analyzed and discussed. Results: We found 197 studies that met the inclusion and exclusion criteria with 2314 participants included in this review. The treatments included topical, oral and procedural. In several studies, hydroquinone alone or combination remains the most effective treatment for melasma. Oral and topical tranexamic acid have been found to be a useful adjuvant treatment in refractory melasma with minimal adverse effects. Procedural treatment such as chemical peels, laser and light-based therapies, and microneedling have a mixed and unpredictable result. Overall, the side effects tend to be mild and affect few of the subject.Conclusions: The current state of the evidence suggests that some treatments with multiple modalities have their respective advantages and disadvantages. The choice of treatment modality must be adjusted according to the type of melasma such as its severity, extent and location. A better understanding of melasma through the further research may improve the therapy options with the least adverse effects.